Genetic profiling of patients with adenoid cystic carcinoma of the Bartholin's glands reveals potential new routes for targeted therapies: a case report - Kohei Nakamura; Eriko Aimono; Shigeki Tanishima; Hidetaka Nomura; Mitsuho Imai; Hideyuki Hayashi; Hiroshi Nishihara (BMC, 2020)
Abstract Background Bartholin gland carcinomas (BGCs) are rare tumor types, for which no molecular analyses including genomic sequencing have been reported to date. Adenoid cystic carcinomas (ACCs) of the Bartholin's glands are an atypical histological type of BGC, and currently nothing is known regarding their genetic profiles or similarity to ACC carcinogenesis in other organs including the salivary glands, thereby limiting possible therapeutic options using precision medicine. Case presentation We used targeted gene sequencing to analyze the occurrence of 160 cancer-related genes in two patients with BG-ACC. KRAS and KDM6A mutations were detected in tumor samples collected from each patient. No KRAS mutations have been previously reported in salivary gland ACCs, indicating that the carcinogenesis of BG-ACC differs from that of the salivary gland ACCs. KDM6A mutations are often reported in salivary gland ACCs and facilitate novel gene-targeted therapy, including the use of BET and HDAC inhibitors. Conclusions A better understanding of the underlying genetic mechanisms will help to clarify the carcinogenesis of BG-ACC. In turn, this will enable treatment with novel targeting agents, as well as the initial exploration of gene-based precision oncological therapies, which aim to improve treatment outcomes for patients with this disease.